2022
DOI: 10.3389/fendo.2021.781543
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin Inhibitory Hormone and Its Receptor: Potential Key to the Integration and Coordination of Metabolic Status and Reproduction

Abstract: Since its discovery as a novel gonadotropin inhibitory peptide in 2000, the central and peripheral roles played by gonadotropin-inhibiting hormone (GnIH) have been significantly expanded. This is highlighted by the wide distribution of its receptor (GnIH-R) within the brain and throughout multiple peripheral organs and tissues. Furthermore, as GnIH is part of the wider RF-amide peptides family, many orthologues have been characterized across vertebrate species, and due to the promiscuity between ligands and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 252 publications
1
9
0
Order By: Relevance
“…Upon light stimulation, decreasing levels of MT results in a decrease in GnIH synthesis ( 69 ), thus alleviating the inhibition on the HPG axis and allowing for the release of GnRH and subsequent activation of gonad development ( 70 ). Consistent with the previous study ( 71 ), we found that chickens with earlier AFE and larger pubic space had higher GnRH content but lower MT content, suggesting that chickens with higher GnRH could give impetus to development of reproductive tissue, contributing to the sexual maturation in crossbreeds. Interestingly, the crossbreeds shared same photoperiod stimulus with purebreds, but exhibited significant heterosis for sexual maturation.…”
Section: Discussionsupporting
confidence: 92%
“…Upon light stimulation, decreasing levels of MT results in a decrease in GnIH synthesis ( 69 ), thus alleviating the inhibition on the HPG axis and allowing for the release of GnRH and subsequent activation of gonad development ( 70 ). Consistent with the previous study ( 71 ), we found that chickens with earlier AFE and larger pubic space had higher GnRH content but lower MT content, suggesting that chickens with higher GnRH could give impetus to development of reproductive tissue, contributing to the sexual maturation in crossbreeds. Interestingly, the crossbreeds shared same photoperiod stimulus with purebreds, but exhibited significant heterosis for sexual maturation.…”
Section: Discussionsupporting
confidence: 92%
“…The results of GPR147 expression experiments in hens agreed with those of our and other previous studies, which demonstrated that the GnIH receptor is expressed in the colon, stomach, and ileum of mice, the intestine of piglets, and the posterior intestine of ratthe tilapia ( Li et al, 2012 ; Muñoz-Cueto et al, 2017 ; Gospodarska et al, 2019 ). In addition to GPR147, GnIH is expressed in the intestine, stomach, and multiple peripheral organs and tissues of several vertebrates ( Wang et al, 2018 ; Bédécarrats et al, 2022 ). These findings suggest that GnIH acts directly on the intestine via its receptor, GPR147, through autocrine and paracrine manner exerting physiological or pharmacological function secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that the constant exposure to a long (red) wavelength, which is known to penetrate the skull more easily to stimulate the HPG axis ( Benoit, 1964 ; Menaker and Underwood, 1976 ; Mobarkey et al, 2010 ), resulted in the desensitization of deep brain photoreceptors. This would effectively impair the activation of the HPG axis, rendering the photoreceptors unable to respond to stimulatory photoperiods or wavelengths, despite the removal of inhibition via GnIH that has been linked to metabolic thresholds ( Bédécarrats et al, 2022 ). Alternatively, it is possible that red light results in an overproduction of GnRH, thus desensitizing its receptor on the anterior pituitary gland.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ferreira et al (2019) demonstrated that broiler breeders remaining under non-stimulatory photoperiods of 8 or 10 h of light will still enter lay at ∼27 woa. This is likely due to the influence of body weight and metabolic factors, which also control the expression of GnIH ( Bédécarrats et al, 2022 ). Thus, it is possible that hens under sRED lighting overcame the desensitization of the photoreceptors.…”
Section: Discussionmentioning
confidence: 99%